2017
DOI: 10.1103/physreve.95.032605
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsoidal Brownian self-driven particles in a magnetic field

Abstract: We study the two-dimensional Brownian dynamics of an ellipsoidal paramagnetic microswimmer moving at low Reynolds number and subject to a magnetic field. Its corresponding mean-square displacement showing the effect of particles's shape, activity, and magnetic field on the microswimmer's diffusion is analytically obtained. The comparison between analytical and computational results display good agreements. In addition, the effect of self-propulsion on the transition time from anisotropic to isotropic diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…An ongoing field of study is the question how the addition of external forces influences the force-free propulsion of active particles. An example are self-propelled particles or particle chains with additional magnetic moments that alter the effective diffusion constant [40] or give rise to new interesting features such as bifurcations and instabilities of linear molecules or rings made of microswimmers [23,41]. A very natural influence to consider is gravity.…”
Section: Introductionmentioning
confidence: 99%
“…An ongoing field of study is the question how the addition of external forces influences the force-free propulsion of active particles. An example are self-propelled particles or particle chains with additional magnetic moments that alter the effective diffusion constant [40] or give rise to new interesting features such as bifurcations and instabilities of linear molecules or rings made of microswimmers [23,41]. A very natural influence to consider is gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Before analyzing the orientational fluctuations in the ribbon, we have first characterized the thermal motion of a single ellipsoid in absence and in presence of an external field. The dynamics of an individual ellipsoid in water has been treated in different works [25][26][27][28][29], and thus here will be only briefly described. In the absence of a magnetic field, the anisotropic shape of the particle causes a non trivial coupling between its rotational and translational motion.…”
Section: Single Particle Dynamicsmentioning
confidence: 99%
“…Active Brownian particle in a Newtonian bath, when subjected to an external magnetic field exhibits exotic transient and steady state properties [57][58][59][60][61][62]. In our previous work, we observed that a harmonically confined active Ornstein-Uhlenbeck particle (AOUP), while selfpropelling in a viscoelastic environment in the presence of a magnetic field features a novel phase transition from diamagnetic to paramagnetic phase [62].…”
Section: Introductionmentioning
confidence: 99%